Manganese-zinc power ferrite material as well as preparation method and application thereof

By adding specific additives and regulation processes to manganese zinc ferrite materials, a high resistance layer and uniform grains are formed, which solves the problem of high loss of manganese zinc ferrite materials under high temperature conditions, and achieves a range of 25-160℃ The low loss characteristics within meet the switching power supply requirements in complex environments.

CN119219406AActive Publication Date: 2024-12-31HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411339016.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing manganese-zeb ferrite materials have high losses under high temperature conditions and cannot maintain low losses within the ultra-wide temperature range above 160℃, making it difficult to meet the needs of switching power supplies in complex environments.

Method used

By adding additives such as SnO2, CaCO3, ZrO2 and Co2O3 to the manganese-zeb power ferrite material, combining the raw material ratio of the main components and the step-by-step mixed sintering process, the components and structure of the material are regulated to form a high resistance layer and uniform crystals. particles, reducing eddy current and hysteresis losses.

Benefits of technology

It realizes low loss characteristics within the ultra-wide temperature range of 25-160℃, especially at high temperature conditions of 160℃, which still has low power consumption, meeting the switching power supply requirements in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to a manganese zinc power ferrite material and a preparation method and application thereof, the manganese zinc power ferrite material comprises main components and additives, the main components comprise Fe2O3, ZnO and MnO, and the additives comprise SnO2, CaCO3, ZrO2 and Co2O3. According to the manganese-zinc power ferrite material and the preparation method thereof, the components of the manganese-zinc power ferrite material are regulated and controlled by matching of the additives, regulation and control of the content and combination of the raw material ratio of the main components, and a step-by-step additive mixing and sintering process is combined, so that the overall loss of the manganese-zinc power ferrite material in an ultra-wide temperature range of 25-160 DEG C is relatively low, that is, the power consumption at 25 DEG C under the conditions of 100 kHz and 200 mT is less than or equal to 360 kW / m < 3 >, and the power consumption at 25 DEG C is less than or equal to 360 kW / m < 3 >. The power consumption at 100 DEG C is less than or equal to 310 kW / m < 3 >, and the power consumption at 160 DEG C is less than or equal
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrite materials, and in particular to a manganese-zinc power ferrite material and a preparation method and application thereof. Background Art

[0002] In recent years, with the improvement of people's environmental awareness, the electric vehicle industry will also usher in a good opportunity for development. The DC-DC converters used in electric vehicles (EV), hybrid electric vehicles (HEV) and fuel cell electric vehicles (FCEV) urgently need a manganese-zinc ferrite material with low loss in an ultra-wide temperature range due to the special use status. This is mainly because the speed of the car is constantly changing during driving, causing the load output power to change at any time. In addition, due to different geographical environments and seasons, the ambient temperature span of the car is also very large, so the temperature of the switching power supply will change all the time in a large temperature range.

[0003] CN102693807A discloses an ultra-wide temperature range, low loss, high magnetic flux density MnZn power ferrite and a preparation method thereof. The main components of the ferrite magnetic material include: Fe2O3: 52-53 mol%, ZnO: 10-12 mol%, MnO: 36-37 mol%, and the additives include: CaCO3: 0.01-0.07 wt%, SnO2: 0.01-0.2 wt%, Nb2O5: 0.01-0.04 wt%, ZrO2: 0.01-0.04 wt%, Co2O3: 0.2-0.55 wt%, V2O5: 0.01-0.05 wt%. The loss Pcv under the conditions of 100 kHz and 200 mT is: 25°C power consumption <390 kW / m 3 , 120℃ power consumption <330kW / m 3 , 140℃ power consumption <400kW / m 3 It only discloses the power consumption below 140°C, and does not involve the power consumption above 140°C, and its high-temperature loss is obviously too high.

[0004] CN102693803A discloses a wide temperature range, low loss MnZn power ferrite and a preparation method thereof. The ferrite is calculated as follows based on the oxides: Fe2O3: 51-54 mol%, MnO: 35-38 mol%, ZnO: 9-13 mol%; the auxiliary components calculated by the total weight of the main components are: CaCO3: 0.03-0.1 wt%, SnO2: 0.02-0.1 wt%, Nb2O5: 0.01-0.04 wt%, ZrO2: 0.01-0.05 wt%, Co2O3: 0.1-0.5 wt%. Under the conditions of 25°C to 120°C, 100 kHz, and 200 mT, the power consumption at 25°C is ≤350 mW / cm 3, 120℃ power consumption ≤350mW / cm 3 It only discloses the power consumption below 120°C, and does not involve the power consumption above 120°C, and its high-temperature loss is still significantly high.

[0005] Therefore, how to provide a manganese-zinc ferrite material with low overall loss in an ultra-wide temperature range of 25 to 160°C, especially at a high temperature of 160°C, which still has low loss, has become a problem that needs to be solved urgently. It is of great significance to meet the use of switching power supplies in complex situations. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a manganese-zinc power ferrite material and a preparation method and application thereof. The present invention adjusts the components of the manganese-zinc power ferrite material by adjusting the coordination and content of the additives and combining the raw material ratio of the main component, and combines the additive step-by-step mixed sintering process, so that the overall loss of the manganese-zinc power ferrite material is low in an ultra-wide temperature range of 25 to 160°C, that is, under the conditions of 100kHz and 200mT, the power consumption at 25°C is ≤360kW / m 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 .

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a manganese-zinc power ferrite material, which includes a main component and an additive, wherein the main component includes Fe2O3, ZnO and MnO, and the additive consists of SnO2, CaCO3, ZrO2 and Co2O3.

[0009] In the present invention, by jointly adding the four additives of SnO2, CaCO3, ZrO2 and Co2O3, the manganese-zinc power ferrite material has the characteristics of wide temperature and low loss, especially under high temperature conditions of 160°C, it still has low loss.

[0010] Among them, by adding CaCO3 and ZrO2 together, they act on the grain boundaries, forming a high resistance layer at the grain boundaries to increase the grain boundary resistivity, thereby reducing eddy current loss, which is more beneficial to improving the high-temperature loss of the material; in addition, the addition of CaCO3 and ZrO2 can also improve the uniformity of the grains, reduce the formation of pores, and thus reduce eddy current loss and hysteresis loss; by adding SnO2 and Co2O3 together, they act on the inside of the grains, Sn 4+ With some Fe 2+ Formation of Sn 4+ -Fe 2+Ion pair, inhibiting Fe 2+ with Fe 3+ The electron transition between Co2O3 and Fe 2+ A synergistic effect is achieved. Since Co2O3 has a positive K1 (magnetocrystalline anisotropy constant), it compensates for the negative K1 value of the manganese-zinc power ferrite material, and the magnetocrystalline anisotropy constant tends to 0, thereby reducing the hysteresis loss.

[0011] The present invention uses a combination of the above-mentioned additives to work simultaneously at the grain boundaries and inside the grains, and combined with the raw material ratio of the main components, together achieves low overall loss in an ultra-wide temperature range of 25 to 160°C, especially under high temperature conditions of 160°C, it still has a low loss effect.

[0012] As a preferred technical solution of the present invention, taking the mass of the main component as 100%, the mass of Fe2O3 is 69.50-69.68wt%, for example, 69.50wt%, 69.52wt%, 69.55wt%, 69.58wt%, 69.60wt%, 69.62wt%, 69.65wt%, or 69.68wt%, etc.

[0013] Preferably, based on 100% by weight of the main component, the weight of ZnO is 5.5-6.4 wt%, for example, 5.5 wt%, 5.8 wt%, 6 wt%, 6.2 wt% or 6.4 wt%.

[0014] Preferably, based on the mass of the main component as 100%, the mass of MnO is 23.6-25.4wt%, for example, 23.6wt%, 23.7wt%, 23.8wt%, 23.9wt%, 24.0wt%, 24.1wt%, 24.2wt%, 24.3wt%, 24.4wt%, 24.5wt%, 24.6wt%, 24.7wt%, 24.8wt%, 24.9wt%, 25.0wt%, 25.1wt%, 25.2wt%, 25.3wt% or 25.4wt%, etc.

[0015] In the present invention, based on the combination of SnO2, CaCO3, ZrO2 and Co2O3 additives, by adjusting the content of the main components, the overall loss of the manganese-zinc power ferrite material is low in an ultra-wide temperature range of 25 to 160°C, that is, under the conditions of 100kHz and 200mT, the power consumption at 25°C is ≤360kW / m 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 .

[0016] Preferably, based on the total mass of the main component, the added amount of SnO2 is 1000-2000 ppm, for example, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm or 2000 ppm.

[0017] Preferably, based on the total mass of the main component, the added amount of CaCO3 is 500-1200 ppm, for example, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, 1100 ppm or 1200 ppm.

[0018] Preferably, based on the total mass of the main component, the added amount of ZrO2 is 100 to 400 ppm, for example, 100 ppm, 150 ppm, 200 ppm, 250 ppm, 300 ppm, 350 ppm or 400 ppm.

[0019] Preferably, based on the total mass of the main component, the added amount of Co2O3 is 3000-4500 ppm, for example, 3000 ppm, 3300 ppm, 3500 ppm, 3800 ppm, 4000 ppm, 4200 ppm or 4500 ppm.

[0020] As a preferred technical solution of the present invention, the manganese-zinc power ferrite material has a power consumption of ≤360kW / m at 25°C under the conditions of 100kHz and 200mT in the temperature range of 25-160°C. 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 .

[0021] In a second aspect, the present invention further provides a method for preparing the manganese-zinc power ferrite material according to the first aspect, the preparation method comprising the following steps:

[0022] (1) mixing the main component and the first additive uniformly, and pre-calcining to obtain a pre-calcined material;

[0023] (2) uniformly mixing the pre-sintered material in step (1) with the second additive to obtain an intermediate powder, and granulating and sintering the intermediate powder to obtain a manganese-zinc power ferrite material;

[0024] Wherein, the main components include Fe2O3, ZnO and MnO;

[0025] The first additive is SnO2 and Co2O3, and the second additive is CaCO3 and ZrO2.

[0026] In the present invention, SnO2 and Co2O3 are first mixed with the main component. Since both act on the inside of the crystal lattice, they are first mixed together to refine the particle size and initially participate in the solid phase reaction during the pre-sintering process, so that the two can enter the inside of the crystal lattice more easily. In addition, considering that there is a part of SnO2 that has not entered the crystal lattice and will segregate in the grain boundary layer, since its melting point is 1127°C, it will form a liquid phase during the sintering process, resulting in rapid growth of the grains and increased porosity. Compared with adding SnO2 in step (2), the advantage of adding SnO2 in step (1) is that it can reduce the segregation of SnO2 in the grain boundary layer, weaken the solid phase reaction, and reduce the porosity.

[0027] By adjusting the preparation process and the coordination and content of various additives in the manganese-zinc power ferrite material, combined with the raw material ratio of the main component, the overall loss is relatively low in an ultra-wide temperature range of 25 to 160°C, especially under high temperature conditions of 160°C, it still has a low loss effect.

[0028] As a preferred technical solution of the present invention, the mixing in step (1) includes sand grinding.

[0029] Preferably, the sanding time is 1 to 2 hours, such as 1 hour, 1.2 hours, 1.5 hours, 1.8 hours or 2 hours.

[0030] Preferably, after the mixing in step (1) and before the pre-firing, drying is also included.

[0031] As a preferred technical solution of the present invention, the pre-calcination temperature in step (1) is 750-850°C, for example, 750°C, 780°C, 800°C, 820°C or 850°C.

[0032] In the present invention, when the pre-firing temperature is 750-850°C, the chemical activity of the powder can be improved, that is, it is easier to carry out solid-phase reaction during the sintering process, which is beneficial to improving the various properties of the manganese-zinc power ferrite material; while a higher pre-firing temperature will make the powder particle size distribution uneven, and discontinuous crystal growth may occur during sintering, which will reduce the performance of the ferrite material; in addition, in order to maintain a uniform particle size of the powder after pre-firing and facilitate subsequent mixing, grinding is required, and a higher pre-firing temperature will also increase the grinding time of the powder after pre-firing.

[0033] Preferably, the pre-burning holding time in step (1) is 2 to 4 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0034] As a preferred technical solution of the present invention, the mixing in step (2) includes sand grinding.

[0035] Preferably, the sanding time is 2 to 4 hours, for example, 2, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0036] As a preferred technical solution of the present invention, after the mixing in step (2) and before granulation, drying is also included.

[0037] Preferably, the median particle size D50 of the powder after drying is 0.9 to 1.2 μm, for example, 0.9 μm, 1.0 μm, 1.1 μm or 1.2 μm.

[0038] Preferably, the granulating agent used in the granulation in step (2) comprises polyvinyl alcohol and / or polyvinyl butyral.

[0039] Preferably, based on the mass of the intermediate powder, the added amount of the granulating agent is 5-10wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.

[0040] As a preferred technical solution of the present invention, the sintering temperature in step (2) is 1260-1300°C, for example, 1260°C, 1270°C, 1280°C, 1290°C or 1300°C.

[0041] Preferably, the sintering holding time in step (2) is 150 to 250 min, for example, 150 min, 180 min, 200 min, 230 min or 250 min.

[0042] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0043] (1) mixing the main component, SnO2 and Co2O3 for 1 to 2 hours, drying, and pre-calcining at 750 to 850°C for 2 to 4 hours to obtain a pre-calcined material;

[0044] Wherein, the main components include Fe2O3, ZnO and MnO;

[0045] (2) mixing the pre-sintered material of step (1) with CaCO3 and ZrO2 for 2 to 4 hours, drying, and obtaining an intermediate powder having a median particle size D50 of 0.9 to 1.2 μm, adding 5 to 10 wt% of a granulating agent based on the mass of the intermediate powder, and sintering at 1260 to 1300° C. for 150 to 250 minutes to obtain a manganese-zinc power ferrite material;

[0046] Wherein, the mixing includes sand grinding; and the granulating agent used in the granulation includes polyvinyl alcohol and / or polyvinyl butyral.

[0047] Compared with the prior art, the present invention has at least the following beneficial effects:

[0048] 1) The manganese-zinc power ferrite material of the present invention has a power consumption of ≤360kW / m at 25°C under the conditions of 100kHz and 200mT within the temperature range of 25-160°C. 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 , especially under high temperature conditions of 160℃, the power consumption is still low;

[0049] 2) The present invention mixes the additives in steps to ensure that the additives acting on the lattice can more easily enter the interior of the lattice and interact with Fe 2+ Form a synergistic effect, reduce the segregation of SnO2 in the grain boundary layer, weaken the solid phase reaction, and reduce the porosity;

[0050] 3) The preparation process of the present invention is simple and low in cost, and the prepared manganese-zinc power ferrite material has the characteristics of wide temperature and low loss. DETAILED DESCRIPTION

[0051] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0053] Example 1

[0054] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, wherein the main components of the manganese-zinc power ferrite material include 69.60wt% of Fe2O3, 6.0wt% of ZnO and 24.4wt% of MnO, and the additives include 1500ppm of SnO2, 1000ppm of CaCO3, 200ppm of ZrO2 and 4000ppm of Co2O3;

[0055] The preparation method comprises the following steps:

[0056] (1) According to the formula, the main components are weighed: 69.60wt% Fe2O3, 6.0wt% ZnO and 24.4wt% MnO (the total mass of the main components is 100%), and the additives are 1500ppm SnO2, 1000ppm CaCO3, 200ppm ZrO2 and 4000ppm Co2O3 (all based on the total mass of the main components);

[0057] The main components Fe2O3, ZnO and MnO, and the additives SnO2 and Co2O3 were mixed and sand-milled for 1 hour, wherein the mass ratio of the total mass of the raw materials, the grinding balls and the water was 1:6:1.5, and then dried and pre-calcined at a temperature of 800°C for 3 hours in an air atmosphere to obtain a pre-calcined material;

[0058] (2) The obtained pre-sintered material, CaCO3 and ZrO2 are mixed and sand-milled for 3 hours, wherein the mass ratio of the total mass of the raw materials, the mass ratio of the grinding balls and the water is 1:6:1.5. After drying, an intermediate powder with a median particle size D50 of 1 μm is obtained. Based on the mass of the intermediate powder, 8 wt% of PVA is added for granulation and molding. The mixture is sintered at 1280°C for 180 min to obtain the manganese-zinc power ferrite material.

[0059] Example 2

[0060] The present embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, wherein the main components of the manganese-zinc power ferrite material include 69.68wt% of Fe2O3, 5.5wt% of ZnO and 24.82wt% of MnO, and the additives include 1200ppm of SnO2, 800ppm of CaCO3, 300ppm of ZrO2 and 3500ppm of Co2O3;

[0061] The preparation method comprises the following steps:

[0062] (1) According to the formula, the main components are weighed: 69.68wt% Fe2O3, 5.5wt% ZnO and 24.82wt% MnO (the total mass of the main components is 100%), and the additives are 1200ppm SnO2, 800ppm CaCO3, 300ppm ZrO2 and 3500ppm Co2O3 (all based on the total mass of the main components);

[0063] The main components Fe2O3, ZnO and MnO, and the additives SnO2 and Co2O3 were mixed and sand-milled for 2 hours, wherein the mass ratio of the total mass of the raw materials, the grinding balls and the water was 1:6:1.5, and then dried and pre-calcined at a temperature of 750°C for 4 hours in an air atmosphere to obtain a pre-calcined material;

[0064] (2) The obtained pre-sintered material, CaCO3 and ZrO2 are mixed and sand-milled for 3 hours, wherein the mass ratio of the total mass of the raw materials, the mass ratio of the grinding balls and the water is 1:5:2. After drying, an intermediate powder with a median particle size D50 of 0.9 μm is obtained. Based on the mass of the intermediate powder, 5 wt% of PVA is added for granulation and molding. The mixture is sintered at 1260°C for 180 minutes to obtain the manganese-zinc power ferrite material.

[0065] Example 3

[0066] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof, wherein the main components of the manganese-zinc power ferrite material include 69.50wt% of Fe2O3, 6.4wt% of ZnO and 24.1wt% of MnO, and the additives include 1800ppm of SnO2, 1200ppm of CaCO3, 400ppm of ZrO2 and 4400ppm of Co2O3;

[0067] The preparation method comprises the following steps:

[0068] (1) According to the formula, the main components are weighed: 69.50wt% Fe2O3, 6.4wt% ZnO and 24.1wt% MnO (the total mass of the main components is 100%), and the additives are 1800ppm SnO2, 1200ppm CaCO3, 400ppm ZrO2 and 4400ppm Co2O3 (all based on the total mass of the main components);

[0069] The main components Fe2O3, ZnO and MnO, and the additives SnO2 and Co2O3 were mixed and sand-milled for 2 hours, wherein the mass ratio of the total mass of the raw materials, the grinding balls and the water was 1:7:1, and then dried and pre-calcined at a temperature of 850°C for 2 hours in an air atmosphere to obtain a pre-calcined material;

[0070] (2) The obtained pre-sintered material, CaCO3 and ZrO2 are mixed and sand-milled for 2 hours, wherein the mass ratio of the total mass of the raw materials, the mass ratio of the grinding balls and the water is 1:7:1. After drying, an intermediate powder with a median particle size D50 of 1.2 μm is obtained. Based on the mass of the intermediate powder, 10 wt% of PVA is added for granulation and molding. The mixture is sintered at 1280°C for 150 min to obtain the manganese-zinc power ferrite material.

[0071] Example 4

[0072] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of SnO2 is 500ppm, and the other components and contents are consistent with those in embodiment 1;

[0073] In the preparation method, the addition amount of SnO2 is adjusted to 500 ppm, and the other preparation methods and parameters are consistent with those in Example 1.

[0074] Example 5

[0075] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of SnO2 is 2500ppm, and the other components and contents are consistent with those in embodiment 1;

[0076] In the preparation method, the addition amount of SnO2 is adjusted to 2500ppm, and the other preparation methods and parameters are consistent with Example 1.

[0077] Example 6

[0078] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of CaCO3 is 300ppm, and the other components and contents are consistent with those in embodiment 1;

[0079] In the preparation method, the addition amount of CaCO3 is adjusted to 300 ppm, and the other preparation methods and parameters are consistent with Example 1.

[0080] Example 7

[0081] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of CaCO3 is 1500ppm, and the other components and contents are consistent with those in embodiment 1;

[0082] In the preparation method, the addition amount of CaCO3 is adjusted to 1500 ppm, and the other preparation methods and parameters are consistent with Example 1.

[0083] Example 8

[0084] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of ZrO2 is 50ppm, and the other components and contents are consistent with embodiment 1;

[0085] In the preparation method, the addition amount of ZrO2 is adjusted to 50 ppm, and the other preparation methods and parameters are consistent with those in Example 1.

[0086] Example 9

[0087] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of ZrO2 is 600ppm, and the other components and contents are consistent with those in embodiment 1;

[0088] In the preparation method, the addition amount of ZrO2 is adjusted to 600 ppm, and the other preparation methods and parameters are consistent with Example 1.

[0089] Example 10

[0090] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of Co2O3 is 2000ppm, and the other components and contents are consistent with those in embodiment 1;

[0091] In the preparation method, the addition amount of Co2O3 is adjusted to 2000ppm, and the other preparation methods and parameters are consistent with Example 1.

[0092] Embodiment 11

[0093] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that the addition amount of Co2O3 is 5000ppm, and the other components and contents are consistent with those in embodiment 1;

[0094] In the preparation method, the addition amount of Co2O3 is adjusted to 5000ppm, and the other preparation methods and parameters are consistent with Example 1.

[0095] Example 12

[0096] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The components and content of the manganese-zinc power ferrite material are consistent with those in Embodiment 1;

[0097] The difference between the preparation method and Example 1 is that in step (1), only SnO2 is first mixed with the main components Fe2O3, ZnO and MnO and sand-ground, and Co2O3 is added in step (2), and the rest of the preparation method and parameters are consistent with Example 1.

[0098] Embodiment 13

[0099] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The components and content of the manganese-zinc power ferrite material are consistent with those in Embodiment 1;

[0100] The difference between the preparation method and Example 1 is that in step (1), only Co2O3 is first mixed with the main components Fe2O3, ZnO and MnO and sand-ground, and SnO2 is added in step (2), and the rest of the preparation method and parameters are consistent with Example 1.

[0101] Embodiment 14

[0102] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The components and content of the manganese-zinc power ferrite material are consistent with those in Embodiment 1;

[0103] The difference between the preparation method and Example 1 is that in step (1), the main components Fe2O3, ZnO and MnO are first mixed, and SnO2 and Co2O3 are added in step (2). The rest of the preparation method and parameters are consistent with Example 1.

[0104] Embodiment 15

[0105] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that, based on the mass of the main component being 100%, the mass proportion of Fe2O3 is 69.30wt%, the mass proportion of MnO is 24.7wt%, and the remaining components and contents are consistent with those in embodiment 1;

[0106] In the preparation method, the mass proportion of Fe2O3 is adjusted to 69.30wt%, the mass proportion of MnO is adjusted to 24.7wt%, and the other preparation methods and parameters are consistent with Example 1.

[0107] Example 16

[0108] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that, based on the mass of the main component being 100%, the mass of Fe2O3 accounts for 69.90wt%, the mass of MnO accounts for 24.1wt%, and the remaining components and contents are consistent with those in embodiment 1;

[0109] In the preparation method, the mass proportion of the Fe2O3 is adjusted to 69.90wt%, the mass proportion of the ZnO is adjusted to 24.1wt%, and the remaining preparation methods and parameters are consistent with those in Example 1.

[0110] Embodiment 17

[0111] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that, based on the mass of the main component being 100%, the mass proportion of ZnO is 5.2wt%, the mass proportion of MnO is 25.2wt%, and the remaining components and contents are consistent with those in embodiment 1;

[0112] In the preparation method, the mass proportion of the ZnO is adjusted to 5.2wt%, the mass proportion of the MnO is adjusted to 25.2wt%, and the other preparation methods and parameters are consistent with those in Example 1.

[0113] Embodiment 18

[0114] This embodiment provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and embodiment 1 is that, based on the mass of the main component being 100%, the mass proportion of ZnO is 6.6wt%, the mass proportion of MnO is 23.8wt%, and the remaining components and contents are consistent with those in embodiment 1;

[0115] In the preparation method, the mass proportion of the ZnO is adjusted to 6.6wt%, the mass proportion of the MnO is adjusted to 23.8wt%, and the other preparation methods and parameters are consistent with those in Example 1.

[0116] Comparative Example 1

[0117] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof. The manganese-zinc power ferrite material is different from Example 1 in that the addition of SnO2 is omitted, and the other components and contents are consistent with those in Example 1;

[0118] In the preparation method, the addition of SnO2 is omitted, and the remaining preparation methods and parameters are consistent with those in Example 1.

[0119] Comparative Example 2

[0120] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof. The manganese-zinc power ferrite material is different from Example 1 in that the addition of ZrO2 is omitted, and the other components and contents are consistent with those in Example 1;

[0121] In the preparation method, the addition of ZrO2 is omitted, and the remaining preparation methods and parameters are consistent with those in Example 1.

[0122] Comparative Example 3

[0123] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and Example 1 is that the addition of Co2O3 is omitted, and the other components and contents are consistent with those in Example 1;

[0124] In the preparation method, the addition of Co2O3 is omitted, and the remaining preparation methods and parameters are consistent with those in Example 1.

[0125] Comparative Example 4

[0126] This comparative example provides a manganese-zinc power ferrite material and a preparation method thereof. The difference between the manganese-zinc power ferrite material and Example 1 is that the addition of CaCO3 is omitted, and the other components and contents are consistent with those in Example 1;

[0127] In the preparation method, the addition of CaCO3 is omitted, and the remaining preparation methods and parameters are consistent with those in Example 1.

[0128] The manganese-zinc power ferrite materials (material standard rings of 25×15×8 mm) provided in Examples 1 to 18 and Comparative Examples 1 to 4 were placed on the SY8219 test equipment, and the test conditions were: 100 kHz, 200 mT, T=25°C, 100°C and 160°C to test their power consumption (kW / m 3 ), see Table 1 for specific data.

[0129] Table 1

[0130]

[0131]

[0132] The test results show that:

[0133] (1) It can be seen from Examples 1-3 that the manganese-zinc power ferrite material of the present invention has a power consumption of ≤360kW / m at 25°C under the conditions of 100kHz and 200mT in the ultra-wide temperature range of 25-160°C. 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 ;

[0134] (2) It can be seen from Examples 1 and 4-11 that the present invention can adjust the addition amounts of SnO2, CaCO3, ZrO2 and Co2O3 within the corresponding ranges, so that the power consumption at each temperature is low, and in particular, the power consumption of the material can be ensured to be ≤360kW / m under high temperature conditions of 160°C. 3 ;

[0135] (3) It can be seen from Examples 1 and 12-14 that the present invention mixes SnO2 and Co2O3 together with the main components Fe2O3, ZnO and MnO, which can work together to refine the particle size and make it easier for the two to enter the lattice. If one of them is added alone or both are added in step (2), the effect of reducing power consumption at each temperature cannot be achieved;

[0136] (4) It can be seen from Examples 1 and 15-18 that the present invention can adjust the content of the main component within a corresponding range to make the power consumption at each temperature lower, and in particular, it can ensure that the power consumption of the material is still ≤310kW / m under high temperature conditions of 100°C. 3 , power consumption is still ≤360kW / m under high temperature conditions of 160℃ 3 ;

[0137] (5) It can be seen from Example 1 and Comparative Examples 1-4 that the additive of the present invention is composed of SnO2, CaCO3, ZrO2 and Co2O3, and the four play a synergistic role at the grain boundaries and inside the grains at the same time. Combined with the raw material ratio of the main components, the overall loss is relatively low in the ultra-wide temperature range of 25 to 160°C, especially under high temperature conditions of 160°C, it still has the effect of low loss. If any one of the additives is omitted, the effect of reducing power consumption at all temperatures cannot be achieved.

[0138] In summary, the present invention adjusts the components of the manganese-zinc power ferrite material by adjusting the coordination and content of the additives, combined with the raw material ratio of the main component, and combined with the step-by-step mixed sintering process of the additives, so that the overall loss of the manganese-zinc power ferrite material is low in an ultra-wide temperature range of 25 to 160°C, that is, the power consumption at 25°C is ≤360kW / m under the conditions of 100kHz and 200mT. 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 .

[0139] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A manganese-zinc power ferrite material, characterized in that: The manganese-zinc power ferrite material comprises a main component and an additive, wherein the main component comprises Fe2O3, ZnO and MnO, and the additive consists of SnO2, CaCO3, ZrO2 and Co2O3.

2. The manganese-zinc power ferrite material according to claim 1, characterized in that: Taking the mass of the main component as 100%, the mass of Fe2O3 is 69.50-69.68wt%; Preferably, based on the mass of the main component being 100%, the mass of ZnO is 5.5-6.4wt%; Preferably, based on the mass of the main component being 100%, the mass of MnO is 23.6-25.4wt%; Preferably, based on the total mass of the main component, the amount of SnO2 added is 1000-2000ppm; Preferably, based on the total mass of the main component, the amount of CaCO3 added is 500 to 1200 ppm; Preferably, based on the total mass of the main component, the amount of ZrO2 added is 100 to 400 ppm; Preferably, based on the total mass of the main component, the added amount of Co2O3 is 3000 to 4500 ppm.

3. The manganese-zinc power ferrite material according to claim 1 or 2, characterized in that: The manganese-zinc power ferrite material has a power consumption of ≤360kW / m at 25°C under the conditions of 100kHz and 200mT within the temperature range of 25-160°C. 3 , 100℃ power consumption ≤310kW / m 3 , 160℃ power consumption ≤360kW / m 3 .

4. A method for preparing the manganese-zinc power ferrite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing the main component and the first additive uniformly, and pre-calcining to obtain a pre-calcined material; (2) uniformly mixing the pre-sintered material of step (1) with the second additive to obtain an intermediate powder, and granulating and sintering the intermediate powder to obtain a manganese-zinc power ferrite material; Wherein, the main components include Fe2O3, ZnO and MnO; The first additive is SnO2 and Co2O3, and the second additive is CaCO3 and ZrO2.

5. The preparation method according to claim 4, characterized in that: The mixing in step (1) includes sand grinding; Preferably, the sanding time is 1 to 2 hours.

6. The preparation method according to claim 4 or 5, characterized in that: The pre-burning temperature in step (1) is 750-850° C. Preferably, the pre-burning holding time in step (1) is 2 to 4 hours; Preferably, the mixing in step (2) comprises sand grinding; Preferably, the sanding time is 2 to 4 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that: After the mixing in step (2) and before granulation, drying is also included; Preferably, the median particle size D50 of the powder after drying is 0.9 to 1.2 μm; Preferably, the granulating agent used in the granulation in step (2) comprises polyvinyl alcohol and / or polyvinyl butyral; Preferably, based on the mass of the intermediate powder, the added amount of the granulating agent is 5 to 10 wt%.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The sintering temperature in step (2) is 1260-1300° C. Preferably, the sintering holding time in step (2) is 150 to 250 minutes.

9. The preparation method according to claim 4, characterized in that: The preparation method comprises the following steps: (1) mixing the main component, SnO2 and Co2O3 for 1 to 2 hours, drying, and pre-calcining at 750 to 850°C for 2 to 4 hours to obtain a pre-calcined material; Wherein, the main components include Fe2O3, ZnO and MnO; (2) mixing the pre-sintered material of step (1) with CaCO3 and ZrO2 for 2 to 4 hours, drying, and obtaining an intermediate powder having a median particle size D50 of 0.9 to 1.2 μm, adding 5 to 10 wt% of a granulating agent based on the mass of the intermediate powder, and sintering at 1260 to 1300° C. for 150 to 250 minutes to obtain a manganese-zinc power ferrite material; Wherein, the mixing includes sand grinding; and the granulating agent used in the granulation includes polyvinyl alcohol and / or polyvinyl butyral.

10. An application of a manganese-zinc power ferrite material, characterized in that: The manganese-zinc power ferrite material described in any one of claims 1 to 3, or the manganese-zinc power ferrite material prepared by the preparation method described in any one of claims 4 to 9, is applied to automotive electronic modules.

Citation Information

Patent Citations

  • Wide-temperature MnZn power ferrite material and preparation method thereof

    CN102693802A

  • Ultra-wide-temperature, low-loss and high-magnetic-flux-density MnZn power ferrite and preparation method thereof

    CN102693807A

  • MnZn ferrite material with relatively high magnetic permeability, wide temperature range and low loss, and preparation method thereof

    CN102745981A

  • Wide-temperature MnZn power ferrite material

    CN102964117A

  • Low-loss manganese zinc ferrite material for temperature of 40 DEG C below zero to 160 DEG C and manufacturing method thereof

    CN104591711A